2021
DOI: 10.3390/plants10081745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrocarbon-Oxidizing Bacteria on the Growth, Biochemical Characteristics, and Hormonal Status of Barley Plants and the Content of Petroleum Hydrocarbons in the Soil

Abstract: Much attention is paid to the relationship between bacteria and plants in the process of the bioremediation of oil-contaminated soils, but the effect of petroleum degrading bacteria that synthesize phytohormones on the content and distribution of these compounds in plants is poorly studied. The goal of the present field experiment was to study the effects of hydrocarbon-oxidizing bacteria that produce auxins on the growth, biochemical characteristics, and hormonal status of barley plants in the presence of oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The slower recovery of vegetation relative to the microbial community can be explained not only by the slower cycles of plant development and reproduction, but also by the relationship between plants and soil microbiota. It is generally assumed that there is a two-way positive relationship between plants and bacteria during the phytoremediation of oil pollution: on the one hand, plants stimulate microbiological activity and, on the other hand, plant-associated microorganisms under these conditions reduce environmental harshness for plants and improve their growth [33,34]. The results of this work, on the one hand, support the relationship between microbiome and vegetation recovery after fuel but, on the other hand, lead us to think about the priority role of one of the components of ecosystems in this process.…”
Section: Discussionmentioning
confidence: 99%
“…The slower recovery of vegetation relative to the microbial community can be explained not only by the slower cycles of plant development and reproduction, but also by the relationship between plants and soil microbiota. It is generally assumed that there is a two-way positive relationship between plants and bacteria during the phytoremediation of oil pollution: on the one hand, plants stimulate microbiological activity and, on the other hand, plant-associated microorganisms under these conditions reduce environmental harshness for plants and improve their growth [33,34]. The results of this work, on the one hand, support the relationship between microbiome and vegetation recovery after fuel but, on the other hand, lead us to think about the priority role of one of the components of ecosystems in this process.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main objectives of the study was to confirm the possibility of increasing the efficiency of phytoremediation by introducing bacteria. The joint use of plants and bacteria for the recultivation of soils contaminated with hydrocarbons is based on the mutually beneficial relationship that exists between them: the plant provides bacteria with easily accessible food sources, while the bacteria help plants survive in a toxic environment, stimulating their growth and reducing the concentration of harmful substances in the soil [ 39 , 55 , 56 ]. Good results have been obtained using biopreparations based on Pseudomonas strains together with plants of the legume family in the restoration of oil-contaminated lands [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Studies showed that soil pollution with kerosene also affects agricultural productivity by adversely affecting soil fertility. 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 Studies showed that soil pollution with kerosene also affects agricultural productivity by adversely affecting soil fertility. 6 Many studies have been dedicated to maintaining ecosystem health and functioning by reclaiming polluted lands and utilizing several restoration technologies. Consequently, mechanical, chemical, and biological approaches have been used to reduce and/or eliminate pollution from petroleum compounds.…”
mentioning
confidence: 99%